Association Between US Physician Malpractice Claims Rates and Hospital Admission Rates Among Patients With Lower-Risk Syncope - Quinn, James (JAMA Netw Open, 2020)
IMPORTANCE: The US Government Accountability Office has changed its estimate of the annual costs of defensive medicine, largely because it has been difficult to objectively measure its impact. Evaluating the association of malpractice claims rates with hospital admission rates and the costs of admitting patients with low-risk conditions would help to document the impact of defensive medicine. Although syncope is a concerning symptom, most patients with syncope have a low risk of adverse outcomes. However, many low-risk patients are still admitted to the hospital, with associated costs of more than $2.5 billion per year in the US. OBJECTIVE: To assess whether hospital admission rates after emergency department visits among patients with lower-risk syncope are associated with state-level variations in malpractice claims rates. DESIGN, SETTING, AND PARTICIPANTS: This cross-sectional study of emergency department visits among patients with lower-risk syncope used deidentified data from the Clinformatics Data Mart database (Optum). Lower-risk syncope visits were defined as those with a primary diagnosis of syncope and collapse based on International Classification of Diseases, Ninth Revision, Clinical Modification code 780.2 or International Classification of Diseases, Tenth Revision, Clinical Modification code R55 that did not include another major diagnostic code for a condition requiring hospital admission (such as heart disease, cancer, or medical shock) or an inpatient hospital stay of more than 3 days. These data were linked to publicly available data from the National Practitioner Data Bank pertaining to physician malpractice claims between January 1, 2008, and December 31, 2017. The 2 data sets were linked at the state-year level. Data were analyzed from October 2, 2019, to September 12, 2020. MAIN OUTCOMES AND MEASURES: The association between the rate of hospital admission after emergency department visits among patients with lower-risk syncope and the rate of physician malpractice claims was assessed at the state-year level using a state-level fixed-effects model. Standardized costs obtained from the Clinformatics Data Mart database were adjusted for inflation and expressed in 2017 US dollars using the Consumer Price Index. RESULTS: Among 40 482 813 emergency department visits between 2008 and 2017, 519 724 visits (1.3%) were associated with syncope. Of those, 234 750 visits (45.2%) met the criteria for lower-risk syncope. The mean (SD) age of patients in the lower-risk cohort was 71.8 (13.5) years; 141 050 patients (60.1%) were female, and 44 115 patients (18.8%) were admitted to the hospital, representing an extra cost of $6542 per admission. The mean rate of physician malpractice claims varied from 0.27 claims per 100 000 people to 8.63 claims per 100 000 people across states and across years within states. A state-level fixed-effects regression model indicated that, for every 1 in 100 000–person increase in the physician malpractice claims rate, there was an absolute increase of 6.70% (95% CI, 4.65%-8.75%) or a relative increase of 35.6% in the hospital admission rate, which represented an additional $102 million in costs associated with this lower-risk cohort. CONCLUSIONS AND RELEVANCE: In this study, increases in physician malpractice claims rates were associated with increases in hospital admission rates and substantial health care costs for patients with lower-risk syncope, and these increases are likely associated with the practice of defensive medicine.